The image of a man in the phraseology of selected Slavic languages - Dopierała, Justyna (Mundus Slavicus I, 2025)
Each community, through its view of the surrounding reality, creates its image of the world, which is reflected in language, more specifically in phraseologisms and proverbs. The units analysed in the article show a generalised image of men in Slavic languages, their physical appearance, external features and relations with women. Regardless of the language, the man is portrayed as the head of the family in a patriarchal model shaped by society and assumes certain characteristics and roles assumed to be typically masculine.